2020
DOI: 10.1155/2020/8853552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Nutrient Sources and NPS Fertilizer on the Agronomic and Economic Performance of Haricot Bean (Phaseolus vulgaris L.) in Southern Ethiopia

Abstract: Despite the fact that mineral fertilizers are widely considered as a major option for addressing the crisis of nutrient depletion, their use among smallholder farmers is not adequate due to an escalating cost. Alternatively, nutrient-rich organic sources that are easily available to farmers are not widely promoted. Thus, this study was carried out in the research field of Wolaita Sodo University, Southern Ethiopia, to evaluate the effects of locally available organic nutrient sources and nitrogen (N) phosphoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Mineral fertilizers are still underutilized in terms of application rates, timing, and fertilizer selection due to their high cost to small-scale farmers, as well as lack of information and training. Aside from that, using mineral fertilizers alone has negative consequences for soil microbes and the environment [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral fertilizers are still underutilized in terms of application rates, timing, and fertilizer selection due to their high cost to small-scale farmers, as well as lack of information and training. Aside from that, using mineral fertilizers alone has negative consequences for soil microbes and the environment [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of integrated nutrient management has reduced the cost of mineral fertilizer by more than half [13]. In view of this, diferent scholars have reported remarkable results from the integrated application of organic and mineral fertilizers, including common bean [11,14,15]. For example, Fouda et al [14] recorded the highest grain yield values of 1681.12 (g) per plot for common bean following an integrated application of NPK 100% + compost.…”
Section: Introductionmentioning
confidence: 99%
“…Our result is also in accord with other findings ( Desta & Almayehu, 2020 ; Hřivna, Kotková & Burešová, 2015 ; Muhammad et al, 2009 ; Tola et al, 2020 ), who stated that the application of fertilizers blended with micronutrients enhanced the vegetative growth of bread wheat and ultimately increased biomass production due to sufficient assimilation process as a result of synergistically balanced nutrient supply. In southern Ethiopia, Elka & Laekemariam (2020) reported increased BY of haricot beans with an increase in the rate of NPS and organic fertilizers. The result is also in agreement with the research findings of others ( Astatke et al, 2004 ; Singh & Wanjari, 2014 ; Tesfaye, Laekemariam & Habte, 2021 ) reported in different soil types.…”
Section: Resultsmentioning
confidence: 99%
“…Nkwanda et al (2021) also noted the strong relationship between water quality degradation and aerial coverage of the water bodies in the Lilongwe River catchment. The scenario depicted in Lake Malombe also applies to other African tropical inland freshwater shallow lakes (Elka & Laekemariam, 2020). For example, in Malawi, reported that Lake Chilwa in Southern Malawi experienced severe water recession due to prolonged dry spells and frequent drought leading to the disruption of ESs.…”
Section: Trade-offs Between Ecosystem Servicesmentioning
confidence: 97%